'I thought if I marry the prophet I would not die': The significance of religious affiliation on marriage, HIV testing, and reproductive health practices among young married women in Zimbabwe. Issue 1 (1st January 2016) - Hallfors, Denise Dion; Iritani, Bonita J.; Zhang, Lei; Hartman, Shane; Luseno, Winnie K.; Mpofu, Elias; Rusakaniko, Simbarashe
Abstract: This study examines the association between religious affiliation and reasons for marriage, perceived church attitudes, and reproductive health-seeking behaviors, including HIV testing, among young women in eastern rural Zimbabwe. The sample comprised women ( N  = 35) who had married by 2012 while participating in a larger randomized controlled trial (RCT) to test the effects of school support on HIV-related risk. The RCT sample was identified in 2007 as all female sixth graders in 25 rural eastern Zimbabwe primary schools whose parents, one or both, had died ( N  = 328). In our previous RCT analyses, we found that participants who affiliated with an Apostolic church were more than four times more likely to marry than those from non-Apostolic churches and that control group participants were twice as likely to marry as those in the intervention group. Other studies had found that marriage greatly increased the odds of HIV infection among adolescent women. Given the link between Apostolic affiliation and marriage, we conducted semi-structured interviews to explore type of marriage, reasons for marrying, church affiliation and attitudes, family planning, HIV testing, schooling, and family life. We were interested in differences, as perceived by our sample of young married women congregants, among Apostolic sects and other denominations in their attitudes about marriage and health-seeking behaviors. We were also interested in the influence of church affiliation on intervention participants' decision to marry, since they had comprehensive school support and education is highly valued in Zimbabwe, but costly and often out of financial reach. Interviews were conducted from October 2012 through November 2013; data were analyzed using a general inductive approach. We found that pressure or perceived deception for coitus or marriage was reported only by intervention participants affiliated with Apostolic denominations. Other reasons for marriage were similar between Apostolic and non-Apostolic adherents, as well as intervention and control conditions. All participants believed HIV testing was important, but while all non-Apostolic denominations encouraged HIV testing and clinic/hospital care, there was considerable heterogeneity in attitudes among Apostolics, with ultraconservative denominations most likely to proscribe non-religious health care. We conclude that some, but not all, Apostolic-affiliated women are afforded discretion in their health-seeking behaviors. Since HIV screening and treatment depend on access to clinic/hospital care, continued public health efforts to engage Apostolic leaders is needed, along with monitoring of progress in access and outcomes.